Israel's place in the Middle East : a pluralist perspective - Rejwan, Nissim (Gainesville, Fla. : University Press of Florida, 1998)
Annotation. To many, Jews & Arabs stand in permanent opposition, representing two clashing cultures, mentalities, & temperaments. In this book, the author maintains that this perception is historically inaccurate. From the standpoint of culture, ethnicity, & religion, he says, Israel is an integral part of the Middle East. As a nation Israel consists largely of Middle Eastern & North African Jews, native-born Israelis of European origin, & Arabs. The author shows that peaceful & neighborly relations among these groups have always prevailed & that the lot of the Jews has been better in the realm of Islam than in the West. Using Arabic, Hebrew, & English sources, the book traces the course of Arab-Jewish relations from their beginnings in pre-Islamic times to the present, & it offers a survey of Judeo-Arabic culture & literature. It also describes the ideological & cultural origins of Israel & demonstrates the way these roots shape the country's attitudes toward its surroundings.
Pan-Arabism Runs its Course. Islam, Democracy, and the Peace Process. Israel's Jewish Identity. Non-Jewish Israelis and Non-Israeli Jews -- Prospect: A Changing Israel in a Pluralist Middle East.
Includes bibliographical references (pages 197-207) and index.
Print version record.
English.
National Jewish Book Awards (won), 1998.
eBooks on EBSCOhost
Keywords: Jewish-Arab relations -- History; Judaism -- Relations -- Islam; Islam -- Relations -- Judaism; Arab-Israeli conflict; Israel -- Politics and government; Israel -- Foreign relations -- Middle East; Middle East -- Foreign relations -- Israel; Palestine question (1948-); Relations judéo-arabes -- Histoire; Judaïsme -- Relations -- Islam; Islam -- Relations -- Judaïsme.; Conflit israélo-arabe.; Israël -- Politique et gouvernement; Moyen-Orient -- Relations extérieures -- Israël.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Arab-Israeli conflict; Diplomatic relations; Interfaith relations; Islam; Jewish-Arab relations; Judaism; Politics and government; Israel; Middle East; Joden; Arabieren; Culturele betrekkingen; Buitenlandse betrekkingen; Midden-Oosten.; Middle East; Regions & Countries - Asia & the Middle East; History & Archaeology; History; Geschiedenis (vorm)